2018
DOI: 10.1002/ejoc.201800779
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Chemo‐ and Regioselective Nitration of Anilides

Abstract: A new and efficient Ag‐catalyzed method for the nitration of anilides by using sodium nitrite as a cheap and available NO2 source has been developed. This C–H functionalization reaction is ortho‐selective, achieves moderate to high yields and shows excellent functional group tolerance. Furthermore, it provides a novel approach to ortho‐nitrated anilides, which are very tricky to access with traditional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Then some of the C atom sites are replaced by N atoms to achieve doping with nitrogen in Ti 3 C 2 T x or NO 2 terminations appear on the surface of Ti 3 C 2 T x . [22,23] Comparison between the nano-Ag@Ti 3 C 2 T x and Ti 3 C 2 T x on the distribution of element is summarized in Table S2 in the Supporting Information. It can also testify that the N appeared after AgNO 3 disintegration.…”
Section: Resultsmentioning
confidence: 99%
“…Then some of the C atom sites are replaced by N atoms to achieve doping with nitrogen in Ti 3 C 2 T x or NO 2 terminations appear on the surface of Ti 3 C 2 T x . [22,23] Comparison between the nano-Ag@Ti 3 C 2 T x and Ti 3 C 2 T x on the distribution of element is summarized in Table S2 in the Supporting Information. It can also testify that the N appeared after AgNO 3 disintegration.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their importance, a number of reliable methods for the preparation benzo[ a ]carbazole derivatives have been developed . Among them, a popular approach is to use diazo compounds as metal carbene precursors to form the required C−C bond(s) in constructing the benzo[ a ]carbazole scaffold ,,.…”
Section: Figurementioning
confidence: 99%
“…For plausible mechanism reported by authors revealed that the reaction initiated by aryl silver complex, which formed via co‐ordination of silver nitrite catalyst and the substrate‘s acetylamino directing group and followed by n‐phenyl acetamide radical, then it reacts with NO 2 + to afford ortho nitrated product. There are several advantages of this approach such as ortho‐selectivity, high functional group tolerance with moderate to higher amount of yield [25] …”
Section: Nitration By C−h Activation Methodsmentioning
confidence: 99%
“…There are several advantages of this approach such as ortho-selectivity, high functional group tolerance with moderate to higher amount of yield. [25] Chun et al have been discovered regioselective nitration of 8-aminoquinoline amide using a palladium catalyst and tertbutyl nitrite under metal-free conditions (Scheme 18). This protocol could be applicable for various aryl, heteroaryl, and also aliphatic carboxamides substrates.…”
Section: Nitration Through Cà H Activationmentioning
confidence: 99%